Inhaled corticosteroids downregulate the SARS-CoV-2 receptor ACE2 in COPD through suppression of type I interferon (2020)
Background: The mechanisms underlying altered susceptibility and propensity to severe Coronavirus disease 2019 (COVID-19) disease in at-risk groups such as patients with chronic obstructive pulmonary disease (COPD) are poorly understood. Inhaled corticosteroids (ICS) are widely used in COPD but the extent to which these therapies protect or expose patients to risk of severe COVID-19 is unknown. Objective: The aim of this study was to evaluate the effect of ICS upon pulmonary expression of the SARS-CoV-2 viral entry receptor angiotensin-converting enzyme (ACE)-2. Methods: We evaluated the effect of ICS administration upon pulmonary ACE2 expression in vitro in human airway epithelial cell cultures and in vivo in mouse models of ICS administration. Mice deficient in the type I interferon-α/β receptor (Ifnar1−/− 56 ) and exogenous interferon-β administration experiments were used to study the functional role of type-I IFN signalling in ACE2 expression. We compared sputum ACE2 expression in patients with COPD stratified according to use or non-use of ICS. Results ICS administration attenuated ACE2 expression in mice, an effect that was reversed by exogenous interferon-β administration and Ifnar1−/− 63 mice had reduced ACE2 expression, indicating that type I interferon contributes mechanistically to this effect. ICS administration attenuated expression of ACE2 in COPD airway epithelial cell cultures and in mice with elastase-induced COPD-like changes. COPD patients taking ICS also had reduced sputum expression of ACE2 compared to non-ICS users. Conclusion: ICS therapies in COPD reduce expression of the SARS-CoV-2 entry receptor ACE2. This effect may thus contribute to altered susceptibility to COVID-19 in patients with COPD.